MTUN and Industry Forum 2009 (FORTUNE 2009) - UMP, PNC (Penerbit UMP, 2009)
The Malaysia Technical Universities Network (MTUN) and Industry Forum (Fourtune 2009) took place at the Eastern & Oriental Hotel, Penang on 15 April 2009. The event was made successful with the cooperation by various technical universities under the MTUN.